A Novel Sequence in the Coiled-coil Domain of Stat3 Essential for Its Nuclear Translocation - Ma, Jing; Zhang, Tong; Novotny-Diermayr, Veronica; Tan, Agnes L.C.; Cao, Xinmin (The Journal of biological chemistry, 2003)
Stat3 is activated by cytokines and growth factors via specific tyrosine phosphorylation, dimerization, and nuclear translocation. However, the mechanism involved in its nuclear translocation is unclear. In this study, by systematic deletion and site-directed mutagenesis we identified Arg-214/215 in the α-helix 2 region of the coiled-coil domain of Stat3 as a novel sequence element essential for its nuclear translocation, stimulated by epidermal growth factor as well as by interleukin-6. Furthermore, we identified Arg-414/417 in the DNA binding domain as also required for the nuclear localization of Stat3. This sequence element corresponds to Lys-410/413 of Stat1, a reported sequence for Stat1 nuclear translocation. On the other hand, Leu-411 of Stat3, corresponding to Leu-407 of Stat1, a necessary residue for Stat1 nuclear transport, is not essential for Stat3 nuclear import. The mutant of Arg-214/215 or Arg-414/417 was shown to be tyrosyl-phosphorylated normally but failed to enter the nucleus in response to epidermal growth factor or interleukin-6. The defect, however, can be rescued by the wild-type Stat3 but cannot be compensated by these two mutants. Mutations on Arg-414/417, but not Arg-214/215, destroy the DNA binding activity of Stat3. Our data for the first time identified a sequence element located in the coiled-coil domain that is involved in the ligand-induced nuclear translocation of Stat3. This novel sequence together with a conserved sequence element in the DNA binding domain coordinates to mediate the nuclear translocation of Stat3.